The Effect of Workload and Work Stress on Employee Performance with Burnout as A Mediation Variable (Case Study at a Health Laboratory in Denpasar City) - Ni Nengah Weni; I Gede Putu Kawiana; I Made Astrama (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This study aims to analyze the effect of workload on employee performance, work stress on employee performance, workload on burnout, work stress on burnout, burnout on employee performance, workload on performance with burnout as a variable, work stress on employee performance by burnout as a mediating variable in Health Laboratory employees in Denpasar City. Using a quantitative approach. Questionnaires that have been tested for validity and reliability are then analyzed using descriptive analysis and inferential analysis with Structural Equation Model-Partial Least Square analysis and produce results. workload has a negative and insignificant effect on employee performance. Work stress has a negative and significant effect on employee performance. Workload has a positive and significant effect on burnout. Job stress has a positive and significant effect on burnout. Burnout has a negative and significant effect on employee performance. Burnout plays a full role capable of mediating the effect of workload on employee performance. This means that burnout is able to perfectly mediate the relationship between workload and employee performance. Burnout plays a role in mediating the effect of work stress on employee performance at the Health Laboratory in Denpasar City.